Resetting Education Policy to Restore Social Mobility - Hisam Kim (Korea Development Institute (KDI), 2015)
Korean society, once characterized by a high degree of intergenerational social mobility, faces increasing pessimism over the significance of one's efforts in moving up the social ladder. Rising skepticism is being cast on the role of education as a pathway to social ascent, given how intergenerational transfer of social status is increasing and the education gap between social classes is widening. Accordingly, the time has come to intervene in the early stages of personal development to prevent wasting talent; to take aggressive measures against inequality; to pursue educational reforms in order to help the younger generations develop competencies and explore diverse paths to success; and to make policy efforts to prevent the social exclusion of the underprivileged. - Low social mobility undermines equality, prohibits an effective distribution of resources, and harms economic growth. - Pessimism has been rising over intergenerational upward mobility, and belief in the significance of an individual's effort has been weakening. - The development of innate cognitive ability varies depending on the environment in which a person is raised. - A gap between social classes and regional representation in admissions has begun to widen at top-tier universities. - The correlation between parental income and children's earnings is marginal for the current middle-aged generation. However, the growing income inequality and race for private education have prompted concerns over intergenerational social mobility. - Intergenerational persistence of income declined during the period of fast economic growth only to increase later. - Belief in the role of education as a ladder of social ascent increased, but has declined in recent years. - To fully realize the potential of underprivileged students, it is necessary to intervene in the early stages of student development and expand affirmative action policies and follow-up support. - The education system should evolve in a way that fosters openness to exploring multiple paths to success. In particular, it is important to diversify the school curriculum and innovate pedagogical paradigms. - Policies should aim at equipping students with basic academic skills, developing useful, relevant skill sets, and expanding public employment services to prevent exclusion of the underprivileged young and maximizing the use of human resources.
Keywords: 330